RF9 Rescues Cortisol-Induced Repression of Testosterone Levels in Adult Male Macaques - Ullah, Rahim; Naz, Rabia; Batool, Aalia; Wazir, Madiha; Rahman, Tanzil Ur; Nabi, Ghulam; Wahab, Fazal; Fu, Junfen; Shahab, Muhammad (Frontiers in Physiology, 2021)
Cortisol inhibits HPG-axis whereas RF9, a potent agonist of kisspeptin receptor (GPR54) activates HPG-axis during fasting-induced stress and under normal physiological conditions. However, the effect of RF9 on the cortisol-induced repressed HPG-axis is not studied yet. This study investigated whether exogenous cortisol-induced repression of the HPG-axis can be rescued by RF9. Six intact adult male rhesus monkeys (Macaca mulatta) habituated to chair-restraint were administered hydrocortisone sodium succinate at a rate of 20mg/kg of body weight (BW) per day for 12 days. Single blood sample was taken by venipuncture from each animal on alternate days for hormones analyses. On experimental day 12, hydrocortisone treated monkeys received a single intravenous bolus of RF9 (n=3) and vehicle (n=3). The animals were bled for a period of 4 h at 60 min intervals from an indwelling cannula in the saphenous vein. RF9 was administered intravenously at the dose of 0.1mg/kg BW immediately after taking 0 min sample. Plasma cortisol and testosterone concentrations were measured by using specific enzyme immunoassays. Hydrocortisone treatment increased plasma cortisol levels (P≤0.0001) and decreased plasma testosterone (P≤0.0127) levels. Interestingly, compared to vehicle, RF9 treatment significantly increased plasma testosterone levels at 120 min (P≤0.0037), 180 min (P≤0.0016) and 240 min (P≤0.0001) intervals in the hydrocortisone treated monkeys. From these results, we concluded that RF9 administration relieves the suppressed HPG-axis in term of plasma testosterone levels in the cortisol treated monkeys.